RIP3, a kinase promoting necroptotic cell death, mediates adverse remodelling after myocardial infarction. (11th June 2014) - Luedde, Mark; Lutz, Matthias; Carter, Natalie; Sosna, Justyna; Jacoby, Christoph; Vucur, Mihael; Gautheron, Jérémie; Roderburg, Christoph; Borg, Nadine; Reisinger, Florian; Hippe, Hans-Joerg; Linkermann, Andreas; et al.
Abstract: Aims: Programmed necrosis (necroptosis) represents a newly identified mechanism of cell death combining features of both apoptosis and necrosis. Like apoptosis, necroptosis is tightly regulated by distinct signalling pathways. A key regulatory role in programmed necrosis has been attributed to interactions of the receptor-interacting protein kinases, RIP1 and RIP3. However, the specific functional role of RIP3-dependent signalling and necroptosis in the heart is unknown. The aims of this study were thus to assess the significance of necroptosis and RIP3 in the context of myocardial ischaemia. Methods and results: Immunoblots revealed strong expression of RIP3 in murine hearts, indicating potential functional significance of this protein in the myocardium. Consistent with a role in promoting necroptosis, adenoviral overexpression of RIP3 in neonatal rat cardiomyocytes and stimulation with TNF-α induced the formation of a complex of RIP1 and RIP3. Moreover, RIP3 overexpression was sufficient to induce necroptosis of cardiomyocytes. In vivo, cardiac expression of RIP3 was up-regulated upon myocardial infarction (MI). Conversely, mice deficient for RIP3 (RIP3 −/− ) showed a significantly better ejection fraction (45 ± 3.6 vs. 32 ± 4.4%, P < 0.05) and less hypertrophy in magnetic resonance imaging studies 30 days after experimental infarction due to left anterior descending coronary artery ligation. This was accompanied by a diminished inflammatory response of infarcted hearts and decreased generation of reactive oxygen species. Conclusion: Here, we show that RIP3-dependent necroptosis modulates post-ischaemic adverse remodelling in a mouse model of MI. This novel signalling pathway may thus be an attractive target for future therapies that aim to limit the adverse consequences of myocardial ischaemia.